Sativalanosteronyl Glycoside and Oryzatriacontolide Constituents from the Hulls of Oryza sativa - CHUNG, ILL-MIN; ALI, MOHD; CHUN, SE-CHUL; LEE, OH-KYU; AHMAD, ATEEQUE (Asian Journal of Chemistry, 2010)
Three compounds sativalanosteronyl glycoside identified as lanost-5, 7, 9(11)-triene-3β-ol-24-one-3β-D-glucopyranoside (1), oryzatriacontolide characterized as n-triacontan-1, 5-olide (2), and tritriaconta-4, 12-diene (3) along with known compound octacosanoic acid were isolated and identified from the rice hulls of Oryza sativa. Their structures were elucidated with the help of 500 MHz NMR using 1D and 2D spectral methods viz., 1H NMR, 13C NMR, HMBC, 1H-1H COSY and HETCOR aided by EI MS, FAB MS and IR.